Pendaftaran Hak Cipta Lagu sebagai Objek Jaminan Fidusa - Kadek Arya Oka Sumantara; I Wayan Novy Purwanto (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Song or Music Copyright with the provisions stipulated in Law Number 42 of 1999 concerning Fiduciary Guarantees, explains that "Song copyrights can be used as Fidusa Guarantees, however in practice, banks refuse to process loans originating from songs and music because so far there are no songs and music that are guaranteed to get a loan, as stipulated in Law Number 10 of 1998 concerning Banking. The purpose of this study is to (1) find out how the classification of song copyrights that can be registered as objects of fidusa guarantees, and (2) find out the model of legal arrangements for song copyrights that are registered as fidusa guarantee objects carried out by banks. The research used to examine this issue is of a normative juridical type and uses statutory and comparative approaches. Indonesian copyright law forms the basis of the legal information used in this research. Some of the data used in this study were collected from various journal papers on song copyright as well as findings from studies on copyright laws. The research findings show that (1) the Copyright Law does not sufficiently explain or describe the process for registering a song copyright as a fidusa guarantee and (2) the Bank's legal policy regarding song copyrights as a fidusa guarantee is based on Article 16 paragraph (3) of the Copyright Law.